The Development of an E-book Based on Local Wisdom Around Bromo Tengger Semeru National Park to Train High School Students' Creative Thinking Skill - Nadya Eka Aristyasari; Yuliani Yuliani; Sifak Indana (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This research aims to produce an e-book based on local wisdom on the use of medicinal plants by the people around Bromo Tengger Semeru National Park on plantae material to train students' creative thinking skills. Method: The research uses the ADDIE development model (analysis, design, development, implementation, and evaluation). Data retrieval through a validation process by three validators, namely education experts, material experts, and biology teachers, practicality through readability tests. Results: The results of the e-book validation get an average high score with very valid criteria. The practicality of the e-book is measured based on the readability test. The readability test results show the readability level at level 10 so that it is suitable for use by grade X students. Novelty: Students' creative thinking skills can be trained by integrating local wisdom with various learning media such as books, modules, and student worksheets, both printed and electronic.